KOMUNIKASI RITUAL PEZIARAH “NGALAP BERKAH”DI KAWASAN WISATA GUNUNG KEMUKUS(Studi Etnografi Komunikasi Tentang Budaya Ritual Ziarah di Kawasan WisataGunung Kemukus, Desa Pendem, Kecamatan Sumber Lawang, Sragen-Jawa Tengah) - Setiawati, Rahmi; Priyanto, Priyanto (Jurnal Vokasi Indonesia, 2015)
This article is explain of ritual commucation pilgrim "ngalap berkah" in the Kemukus mountain, ethnographic study of communication about cultural tourism zone ritual pilgrimage in Mount Kemukus, Pendem Village, District Sumber Lawang, Sragen, Central Java. The results showed that for the local community a message of what is hidden behind this ritual is still ambiguity. But in the process of social interaction between indigenous communities with immigrant communities, both in terms of livelihoods, different behavior patterns, causing local people trying to accept changes to the meaning of "ngalap berkah". It is caused when the pilgrimage locations have changed or constructed for tourist commodification, and is thought to enhance the growth of local economies, which have an impact on improving social and economic conditions of the communities in Pendem.